Archaeometric investigation of the hoard from Bodrogolaszi, Hungary. Issue 2 (21st December 2015) - Nagy, Zsolt Dezső; May, Zoltán; Fintor, Krisztián
Abstract: The hoard from Bodrogolaszi is a very significant find, dating back to the 15 th -16 th centuries. Unfortunately only 73 coins have survived from the original 135. In our study we would like to present the site, the circumstances of finding the hoard, and also a short numismatic introduction to these coins. We used stereomicroscopy to investigate the surface of coins, searching for additional artificial interventions (breaking, cutting, and fillip). We discovered darker reddish brown spots on several coins. We applied Raman spectroscopy to determine the origin of the spots. The results revealed they are part of a lepidocrocitegoethite cover layer caused by exposure to the soil. XRF measurements were used to prove that the purity of the coins differs from historical data.